Elucidation of the Amygdalin Pathway Reveals the Metabolic Basis of Bitter and Sweet Almonds (Prunus dulcis). Issue 3 (8th October 2018) - Thodberg, Sara; Del Cueto, Jorge; Mazzeo, Rosa; Pavan, Stefano; Lotti, Concetta; Dicenta, Federico; Jakobsen Neilson, Elizabeth H.; Møller, Birger Lindberg; Sánchez-Pérez, Raquel
Abstract : Two missing enzyme activities in the amygdalan pathway result in sweet versus formation of bitter almonds. Abstract: Almond ( Prunus dulcis ) is the principal Prunus species in which the consumed and thus commercially important part of the fruit is the kernel. As a result of continued selection, the vast majority of almonds have a nonbitter kernel. However, in the field, there are trees carrying bitter kernels, which are toxic to humans and, consequently, need to be removed. The toxicity of bitter almonds is caused by the accumulation of the cyanogenic diglucoside amygdalin, which releases toxic hydrogen cyanide upon hydrolysis. In this study, we identified and characterized the enzymes involved in the amygdalin biosynthetic pathway: PdCYP79D16 and PdCYP71AN24 as the cytochrome P450 (CYP) enzymes catalyzing phenylalanine-to-mandelonitrile conversion, PdUGT94AF3 as an additional monoglucosyl transferase (UGT) catalyzing prunasin formation, and PdUGT94AF1 and PdUGT94AF2 as the two enzymes catalyzing amygdalin formation from prunasin. This was accomplished by constructing a sequence database containing UGTs known, or predicted, to catalyze a β(1→6)- O -glycosylation reaction and a Basic Local Alignment Search Tool search of the draft version of the almond genome versus these sequences. Functional characterization of candidate genes was achieved by transient expression in Nicotiana benthamiana . Reverse transcription quantitative polymerase chain reaction demonstrated that the expression of PdCYP79D16 and PdCYP71AN24 was not detectable or only reached minute levels in the sweet almond genotype during fruit development, while it was high and consistent in the bitter genotype. Therefore, the basis for the sweet kernel phenotype is a lack of expression of the genes encoding the two CYPs catalyzing the first steps in amygdalin biosynthesis.